Civic-related factors as determinants of NCE students' attitude to citizenship education (2024)
This study examines the relative and composite contributions of civic engagement, civic values and political attitudes to pre-service teachers' attitudes to citizenship education in colleges of education in Oyo State, Nigeria. The survey research design of correlational type was adopted for the study. One Federal and one State-owned colleges of education located at different towns in Oyo State were purposively selected. Two hundred and fifty NCE II pre-service teachers were randomly selected from each of the institution. The instruments used were: civic engagement questionnaire (r = 0.78), civic values questionnaire (r = 0.81), political attitude scale (r - 0.75), and citizenship education attitude scale (r = 0.76). Data were analysed using Pearson Product Moment Correlation and Multiple Regression Analysis at 0.05 level of significance. There was a positive significant relationship between each of students' civic engagement (r = .108, p<.0I5) and students' civic value (r = .102. p<.05) and students' attitude towards citizenship education. The civic-related factors made a significant (F3.49; Adj. R2 = .016; p<.05) joint contribution (R = . 149', R2 = .022) to students' attitude to citizenship education. Students' civic engagement (β .112, t = 2.533, p<.05) and students' civic value (β = .096, t = 2.170, p<.05) made significant relative contributions and predicted students' attitude towards citizenship education, while students' political attitude did not. It is concluded that civic engagement and civic value determined pre-service teachers' attitude towards citizenship education. It is recommended that strategies which promote civic engagement and inculcation of civic values should be adopted to enhance NCE students' attitude towards citizenship education in colleges of education.